Eksplorasi Kegiatan Saving Soul dalam Pembelajaran Matematika Berbasis STEM (Journal of Madrasah Studies, 2024)
STEM learning plays an important role in 21st century education. Teachers as one of the key aspects of education implementation play an important role in the implementation of STEM learning. This study aims to explore saving soul activities in STEM-based mathematics learning in elementary madrasahs. This study is a descriptive qualitative study with an observation method. The data collection process was carried out through a questionnaire regarding the implementation of STEM learning and activities carried out in learning. The results of the study showed that saving soul activities in STEM-based Mathematics learning were carried out by practicing student-centered learning, learning with inquiry and problem-based models, evaluation, reflection, collaboration, and implementing integrated learning both in terms of content and skills. Teachers have carried out learning activities that lead to STEM learning through saving soul activities carried out in the classroom. the teacher makes good preparations for learning activities, then prepares a learning plan and learning steps that are accompanied by teacher and student activities during the learning process. Furthermore, exploring saving soul activities by describing in detail the mathematics learning process that is carried out. During the learning process, it has also shown the uniqueness of STEM in learning.